2018
DOI: 10.3846/gac.2018.2023
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of the Estonian National GNSS Reference Station Network

Abstract: The first GNSS (Global Navigation Satellite System) CORS (Continuously Operating Reference Station) in Estonia became operational in 1996. Starting from 2008 four Estonian CORS are incorporated into the EPN (EUREF Permanent GNSS Network). During the years 2014-2015 modernization of the GNSS CORS in Estonia was carried out. Currently the total number of the resulting ESTPOS reference stations is 28. These ESTPOS stations were interconnected to the I order national geodetic network by a special GNSS campaign in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The airborne GNSS and inertial measurement unit datasets were utilised for flight trajectory calculations with respect to the nearby Estonian national GNSS reference stations (Metsar et al, 2018). The RIEGL RiProcess software and standard workflow (e.g., Gruno et al, 2013) were used to compute 3D coordinated point clouds that depict instantaneous SSH (with respect to the reference ellipsoid GRS-80).…”
Section: )mentioning
confidence: 99%
“…The airborne GNSS and inertial measurement unit datasets were utilised for flight trajectory calculations with respect to the nearby Estonian national GNSS reference stations (Metsar et al, 2018). The RIEGL RiProcess software and standard workflow (e.g., Gruno et al, 2013) were used to compute 3D coordinated point clouds that depict instantaneous SSH (with respect to the reference ellipsoid GRS-80).…”
Section: )mentioning
confidence: 99%
“…The fixed-wing platform also had an on-board Global Navigation Satellite System Real-time Kinematic/Post-Processed Kinematic (GNSS RTK/PPK) receiver activated. Data recorded during the flights were subsequently post-processed using differential correction data (RINEX) provided by the Estonian Land Board's virtual reference stations [27]. We opted for this approach based on Tomaštík et al [21] findings, which reported higher horizontal and vertical accuracies using PPK than using ground control points (GCP).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The UAS data was post-processed in SenseFly eMotion 3 [40] using receiver independent exchange (RINEX) format data provided by the GNSS CORS (Continuously Operating Reference Station) of Estonia [41] for post-processing kinematics (PPK) corrections. This post-process provided an increase in the geotagging accuracy [42] of the UAS images from 5 m error to under 0.06 m, where the method and accuracy obtained is similar to [43]; and thus less than the one-pixel size in our study.…”
Section: Image Processing and Analysismentioning
confidence: 99%